Simple Spectrophotometric Determination of Phenol in Industrial Waste Water - Chakravarty, Sumon; Kanti Deb, Manas; Mishra, R.K. (Asian Journal of Chemistry, 2012)
A new simple, selective and rapid spectrophotometric method for the determination of phenol in trace amounts has been described. The method is based on the colour reaction of phenol with 1,2-naphthaquinone-4-sulphonic acid (NS) in alkaline medium at pH 8.7-9.3, to give bluish-green indophenol dye. The dye produced has a maximum absorbance at 650 nm. The method obeys Beer’s law up to 6.0 μg phenol ml-1 in aqueous phase. The molar absorptivity of the method is 1.4 × 104 mol-1 cm-1. The detection limit of the method is 0.05 μg phenol ml-1. The method is reproducible and the relative standard deviation of the method for 10 replicate measurements is 0.97%. Various analytical parameters have been studied to find the optimum condition for determining trace amounts of phenol in the industrial waste water.